Professional Firm Publications. - Scheiner, James H. (The Accounting Review, 1978)
The article presents a new series designed to highlight accounting firms' publications of possible interest to academics. In recent years the largest public accounting firms have increased both the quantity and the quality of their accounting publications. Since such publications are ordinarily on topical subjects, they can be helpful to both the educator and the researcher. A Guide for Studying and Evaluating Internal Accounting Controls, published by Arthur Andersen & Co., uses five interrelated business cycles: treasury, expenditure, conversion, revenue and financial reporting, and a financial planning and control function to structure a framework based upon transactions for studying and evaluating internal control. Financial Statement Disclosure Checklist-1978 is designed to serve as a "memory jogger" for preparing and/or reviewing financial statements. Corporate Audit Committees: Policies and Practices reports the results of a survey of almost 1000 chief executive officers, internal auditors, independent CPAs, and non-officer directors and an examination of other publicly available information.